2023
DOI: 10.1136/bjsports-2022-106409
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dose and type of physical activity to improve functional capacity and minimise adverse events in acutely hospitalised older adults: a systematic review with dose-response network meta-analysis of randomised controlled trials

Abstract: ObjectiveTo identify the optimal dose and type of physical activity to improve functional capacity and reduce adverse events in acutely hospitalised older adults.DesignSystematic review and Bayesian model-based network meta-analysis.Data sourcesFour databases were searched from inception to 20 June 2022.Eligibility criteria for selecting studiesRandomised controlled trials that assessed the effectiveness of a physical activity-based intervention on at least one functional outcome in people aged ≥50 years hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…For a better understanding of this terminology, we are going to apply different standardization methods on data extracted from a published meta‐analysis [4]. Therefore, we select the Ortiz‐Alonso et al study [5] included in this meta‐analysis, which reported results using the overall score of the Short Physical Performance Battery (an instrument to assess the physical function; SPPB), and extract the “raw” data (i.e., data directly extracted from the study without any transformation) (Table 1).…”
Section: How To Compute Standardized Mean Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…For a better understanding of this terminology, we are going to apply different standardization methods on data extracted from a published meta‐analysis [4]. Therefore, we select the Ortiz‐Alonso et al study [5] included in this meta‐analysis, which reported results using the overall score of the Short Physical Performance Battery (an instrument to assess the physical function; SPPB), and extract the “raw” data (i.e., data directly extracted from the study without any transformation) (Table 1).…”
Section: How To Compute Standardized Mean Differencesmentioning
confidence: 99%
“…We then re‐express this effect size into SPPB units multiplying by the external SD reference for the study population (external SD reference = 3.14), obtaining a scale‐specific pooled effect of MD = 0.97 (95% CI: 0.06–2.42). Considering a predefined minimally clinically important difference of 1 point in the SPPB, [9] we could support the use of an intervention (physical activity in this case [4]) in a specific population due to its clinically meaningful benefit in the outcome of interest.…”
Section: How To Interpret Standardized Mean Differencesmentioning
confidence: 99%
“…The levels of physical activity were not associated with readmission within 30 days. Existing literature emphasizes the advantages of physical activity during hospitalization, not only for patients with hip fracture [2,6,50,51]. We therefore need a deeper understanding and clarification of clinical practices concerning mobility and physical activity, specifically focusing on reasons for lack of activity.…”
Section: Discussionmentioning
confidence: 99%
“…Such excessive time spent in bed may lead to an accelerated development of sarcopenia, frailty, and physical function decline [5,7,8]. Physical exercise plays an essential role in preventing these health consequences in older hospitalized patients [9,10]. A metaanalysis of Randomized Controlled Trials (RCTs) concluded that 25-50 minutes a day of slowpaced walking or multicomponent exercise at the hospital can improve functional capacity and reduce the number of adverse events for older adults [10].…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise plays an essential role in preventing these health consequences in older hospitalized patients [9,10]. A metaanalysis of Randomized Controlled Trials (RCTs) concluded that 25-50 minutes a day of slowpaced walking or multicomponent exercise at the hospital can improve functional capacity and reduce the number of adverse events for older adults [10]. It can however be challenging to find feasible interventions for older people with limited physical capacity [11].…”
Section: Introductionmentioning
confidence: 99%